Study on the Fast Transient Process of Primary Equipment Operation in UHV Fixed Series Capacitors Based on PEEC Method - Baojiang Tian; Kai Xu; Yingying Wang; Pei Guo; Chao Xiao; Wei Han; Yiran Dong; Jingang Wang (Sensors)
This manuscript proposes a fast transient simulation method based on PEEC to model overvoltage caused by spark gap and disconnecting switch operations in UHV series compensation (FSC). It proposes a simulation method based on the Partial Element Equivalent Circuit (PEEC) for modeling the fast transient processes associated with the operation of primary equipment in UHV FSC. Initially, a multi-conductor system model for both primary and secondary equipment on the cascade platform is developed. Then, the lumped components′ modeling of primary equipment and secondary equipment is added on the basis of multi-conductor model. Through simulation, the rapid transient overvoltage of primary equipment and the electromagnetic disturbance of the secondary system are analyzed. The simulation results provide insights into the distribution of fast transient overvoltage and the transient electromagnetic disturbance along the bus, from the low-voltage bus to the high-potential platform, under various primary equipment operating conditions. These findings provide a basis for theoretical analysis of the layout of sensor devices on platform and the design of electromagnetic shielding for interference-prone systems on platform.